IMPLEMENTASI SISTEM MONITORING KOORDINAT LATITUDE DAN LONGITUDE BERBASIS INTERNET OF THINGS(IOT) SECARA REALTIME - Rindah Sulasmi; Desyderius Minggu; Muhamat Maariful Huda (Jurnal Telkommil, 2021)
Nowadays, the virtual world is not something new. The role of the virtual world relies heavily depend on communication to report the situation and condition as soon as the position of soldiers in the military world, to carrying out their assignments and training. To support this task, a tool for determining coordinates using HT (Handy Talky) was made by transmitting real-time GPS (Global Position System) data based on IoT (Internet of Things) using the internet protocol network as the transmission medium. With the GPS system, latitude and longitude data will be obtained from the GPS module. The results of data will be processed by the Microcontroller, which we use the Arduino Pro Micro module then sent to the Monitoring server which will be shown in the form of mapping and show coordinate data, observers can monitor the position of field personnel who are carrying out patrols according to their area.